Synthesis of Chiral Tricarbonylchromium(0) Aromatic Aldehydes and Their Asymmetric Aldol Reaction with Acetone - Shi, Jing-jing; Zhao, Ling-Ling; Zhang, Xiao-Xiao; Wang, Chao; Wan, Yu; Xu, Zhou; Wu, Hui (Asian Journal of Chemistry, 2011)
The preparation of chiral tricarbonylchromium(0) aromatic aldehydes was improved in a shorter total time with higher yields comparing with previous methods. Their asymmetric aldol reactions with acetone were studied at room temperature.